แนวทางการจัดการงานบำรุงรักษาทางขององค์การบริหารส่วนจังหวัด และเทศบาลนคร - เจนวิทย์ พงศ์จรรยานุกูล (จุฬาลงกรณ์มหาวิทยาลัย, 2011)
The Act of Decentralized Planning Process B.E. 2542(1999) reinfores to transfer road maintenance responsibilities to the local governments. However, there are problems from the lack of ability and readiness to take care of the roads by local governments. Thus, the objective of the research is to analyze the problems by interview and questionnaire in order to propose guideline for managing the maintenance workload in responsibilities and consistent with the limitation of current operations. The conclusion form the interviews of 11 local governments at all levels can be drawn as a result of lack of staff with overwhelm workload, lack of technical in road maintenance (data collection, condition Inspection, performance analysis, and maintenance analysis), lack of funding and equipments, internal operations (planning and maintenance operation, report preparation, road supervision) and rapid deterioration of roads are the problems in current operations. Questionnaires results from 35 of Provincial Administrative Organizations (PAOs) and 10 of Municipalities showed the difference between two organizations. PAOs have staff less than Municipalities and they also have authority in territory more than Municipalities. The results from studying of problems and current maintenance operations have been analyzed by using Cause and Effect diagram. Then, the past pavement maintenance management systems and technology were used to solve the problems. In addition, a developed guideline was used which consists of 6 components as follows: (1) Database, which solves operational issues in the data collection, scattered and lost of information (2) Conditions Inspection and (3) Performance Analysis, which solve the lack of staff and reduce the work process (4) Maintenance Analysis, which solves the lack of machine and proper maintenance (5) System Planning, which solves the lack of funding and allocation of the limited budget (6) Implementation and Monitoring which solve planning and monitoring of maintenance process. Due to the difference of problems between two organizations, the composition of the Conditions Inspection and Performance Analysis are different. PAOs were found to be appropriate with inspection technology to examine the damage. However, since roads are limited to the area and taken care of thoroughly, the visual inspection is the best procedure for Municipalities. In addition, researcher proposes the guideline to Nontaburi PAO and Nontaburi Municipality to determine the feasibility in practice and had accepted the guidelines. However, Nontaburi Municipality realized that System Planning and Implementation with Monitoring are not appropriate in present because there is no responsible department for maintenance, and the complaints from the public must be the first priority.